Association between SLC11A1 polymorphisms and susceptibility to different clinical forms of tuberculosis in the Peruvian population - Taype C.A. (2006)
This study was supported by Proyecto Vig?´a MINSA/USAID, Lima; Premio Anual de Medicina Francisco Tejada y Sem?´ramis Rea´tegui (Facultad de Medicina Alberto Hurtado, Universidad Peruana Cayetano Heredia, UPCH), Lima; Fundacio´n Instituto Hipo´lito Unanue, Lima and Consejo Nacional de Ciencia y Tecnolog?´a (CONCYTEC), Lima-Peru´. CT received support from CONCYETC, the Agreement between Consortium of Francophones Universities of Belgium (CIUF) and UPCH, and the Fundacio´n Cristina e Ismael Cobia´n (Facultad de Ciencias y Filosof?´a Alberto Cazorla Ta´lleri, UPCH). We are very grateful to Dr. Rupert Quinnell for valuable suggestions to this paper.